Body Composition of Tambaqui, Colossoma macropomum, and Matrinxã, Brycon cephalus, When Raised in Intensive (Igarapé Channel) and Semi-Intensive (Pond) Culture Systems - Arbeláez-Rojas, Gustavo Alberto (Revista Brasileira de Zootecnia, 2020)
This study analyzed the influence of the fish farming system (intensive, in igarapé channel, or semi-intensive, in ponds) on the body composition of tambaqui, Colossoma macropomum, and matrinxã, Brycon cephalus, juveniles. Tambaqui (15.4 cm and 88.3 g average length and weight, respectively) and matrinxã (23.4 cm and 219.4 g average length and weight, respectively) were stocked at a density of 10 and 1 fish/m2 in the intensive and semi-intensive culture system, respectively. Fish were fed to satiation, twice a day, a 30% crude protein comercial extruded feed, for 170 days. The proximate analysis of the edible portion (fillet) and the whole fish, at the end of the culture period, showed less fat deposition and higher protein retention for matrinxã and tambaqui raised in the intensive system. Weight gain was different between the two species, depending on the culture system: tambaqui showed significantly higher in weight gain when raised in the semi-intensive system, whereas matrinxã weight gain was not different in both culture systems.